Empowering Garut's Entrepreneurs: A Community Engagement Initiative through the WiraHebat Digital Marketing Training - Asep Koswara (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
This study reports on a community service activity aimed at enhancing the digital capability of MSME actors in Garut, Indonesia, conducted on November 19, 2025, as part of the WiraHebat Goes to Village program. Addressing the local digital gap, the intervention utilized a practitioner-led training titled,